2018
DOI: 10.1002/cssc.201800641
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient and Robust Perovskite Anode with Iron–Palladium Co‐exsolutions for Intermediate‐Temperature Solid‐Oxide Fuel Cells

Abstract: The low performance and insufficient catalytic activity of perovskite anodes hinder their further application in intermediate-temperature solid-oxide fuel cells (IT-SOFCs). A novel La Sr Fe Nb Pd O (LSFNP) anode material has been developed with Fe-Pd co-exsolutions for IT-SOFCs. Fe and Pd metallic nanoparticles are confirmed to exsolve on the surface of the perovskite anode during operation under a hydrogen atmosphere. The introduced Pd exsolutions promote the charge-transfer process slightly and the H -adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Indeed, Li et al detail the co-ex-solution process of Pd and Fe in which the elements did not form a solid solution but were anchored individually on the oxide support of La 0.8 Sr 0.2 Fe 0.9 Nb 0.1 Pd 0.04 O 3−δ . 81 Similarly, Pd and Ni do not form a homogeneous alloy but rather take the shape of a core−shell structure, as reported by Buharon et al 64 The scenario becomes more complicated when more than two constituents form alloy. For the Cu 1−x Ni x Fe 2 O 4 spinel oxide, Kang et al reported the two different phases of ex-solved alloys: independent Cu-rich and Fe-rich ternary CuFeNi alloys during a reductive heat treatment.…”
Section: Multicomponent Ex-solutionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, Li et al detail the co-ex-solution process of Pd and Fe in which the elements did not form a solid solution but were anchored individually on the oxide support of La 0.8 Sr 0.2 Fe 0.9 Nb 0.1 Pd 0.04 O 3−δ . 81 Similarly, Pd and Ni do not form a homogeneous alloy but rather take the shape of a core−shell structure, as reported by Buharon et al 64 The scenario becomes more complicated when more than two constituents form alloy. For the Cu 1−x Ni x Fe 2 O 4 spinel oxide, Kang et al reported the two different phases of ex-solved alloys: independent Cu-rich and Fe-rich ternary CuFeNi alloys during a reductive heat treatment.…”
Section: Multicomponent Ex-solutionmentioning
confidence: 85%
“…Moreover, immiscibility between the metal components is another important issue to determine whether the metal ex-solutes will form a homogeneous alloy. Indeed, Li et al detail the co-ex-solution process of Pd and Fe in which the elements did not form a solid solution but were anchored individually on the oxide support of La 0.8 Sr 0.2 Fe 0.9 Nb 0.1 Pd 0.04 O 3−δ . Similarly, Pd and Ni do not form a homogeneous alloy but rather take the shape of a core–shell structure, as reported by Buharon et al The scenario becomes more complicated when more than two constituents form alloy.…”
Section: Multicomponent Ex-solutionmentioning
confidence: 98%
“…After reduction, the Ti 4+ (0.605 Å) ions are partially reduced to Ti 3+ (0.670 Å), which may lead to a longer bond. 41,42 On the other hand, the generated oxygen vacancies may also have an effect on the volume expansion of the lattice. 19,43 XPS was performed to study the changes in the valence states of B-site elements.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the XRD refinement data (Figure b,c) shows that the LSTMC lattice expanded after reduction. After reduction, the Ti 4+ (0.605 Å) ions are partially reduced to Ti 3+ (0.670 Å), which may lead to a longer bond. , On the other hand, the generated oxygen vacancies may also have an effect on the volume expansion of the lattice. , …”
Section: Resultsmentioning
confidence: 99%
“…The ex-solution phenomenon has received much attention as a way to enhance the durability of supported metal catalysts. , It involves a phase transition during which metal atoms doped in the lattices of metal oxides, most notably perovskites, are extracted out upon reduction process, and the atoms often move back to the original position upon oxidation. , The metal catalysts prepared by the ex-solution show good durability upon high temperature reactions, because the metals segregated from the parent support are anchored into the lattice and not just deposited on the surface of the support. These “socketed” nanoparticles demonstrated sintering or coking tolerance due to strong interaction with the parent support, compared to conventional catalysts on which metal nanoparticles are simply deposited on the support. Several metal catalysts prepared by this ex-solution have been reported to be stable under long-term reactions at high temperatures .…”
Section: Introductionmentioning
confidence: 99%